Real-Life Experience With First-Line Therapy Bortezomib Plus Melphalan and Prednisone in Elderly Patients With Newly Diagnosed Multiple Myeloma Ineligible for High Dose Chemotherapy With Autologous Stem-Cell Transplantation - Buda, Gabriele; Del Giudice, Maria Livia; Antonioli, Elisabetta; Ghio, Francesco; Orciuolo, Enrico; Morganti, Riccardo; Martini, Francesca; Staderini, Michela; Galimberti, Sara; Petrini, Mario (Frontiers in Medicine, 2021)
Currently, the regimen with bortezomib plus melphalan and prednisone (VMP) is a standard treatment for multiple myeloma and it is recommended as the first‐line therapy for patients with multiple myeloma ineligible for high‐dose chemotherapy with autologous stem‐cell transplantation. Objectives Participants of the clinical trial are highly selected populations; therefore, the aim of this study was to present observations from real practice that can provide important information for practitioners and to investigate clinical outcomes of VMP regimen in elderly patients with newly diagnosed MM. Patients and methods We retrospectively analyzed the data on the efficacy and survival parameters, such as overall survival (OS) and event-free survival (EFS), with attention to the effect of gender, age and International Staging System (ISS) stage, of VMP regimen in 164 patients with newly diagnosed multiple myeloma not eligible for high‐dose chemotherapy with autologous stem‐cell transplantation (median age, 75 years; range, 60–86 years). Results Patients aged 75 years or older constituted 50.6% of the study cohort. Frail patients were 10.36%, according to the clinical frailty scale of geriatric assessment (GA). A total of 1203 courses of VMP regimen (mainly VMP 1-29, 99.16 %) were administered. The median cumulative delivered dose of bortezomib was 46.8 mg/m2. The overall response rate (ORR), including all patients with a partial response or better, was 81.7% and the complete response rate (CRR) was 10.36 %. After a median 38.51 months of follow-up, the median overall survival (OS) was 34.33 months; the median event-free survival (EFS) after VMP and second-line therapy (mainly Rd, 56.31%) were 18.51 and 10.75 months, respectively. In the subgroup of patients with 75 years or older the median OS was 29.76 months; the median EFS after first and second-line therapy were 17.76 and 8.93 months respectively. The hazard ratio for OS was 2.276 (p value 0.046) and for EFS was 1.507 (p value 0.055) for the ISS stage II and III group. Age and gender were not negative predictors of survival. Conclusions VMP treatment is highly effective in the first-line therapy of elderly patients with multiple myeloma ineligible for HDT with auto‐SCT.